Leadership and Regional Security Architecture: Between Strategic Stability and Defense Diplomacy - Goga, Alin Mihăiță (Acta Universitatis Danubius. Relationes Internationales, 2025)
This study explores the critical interface between military leadership and regional security architecture, arguing that the strategic decisions of military leaders not only shape operational effectiveness but also exert a profound influence on diplomatic dynamics within multilateral defense frameworks. By analyzing command structures, defense diplomacy initiatives, and regional interoperability mechanisms across distinct case contexts, the article demonstrates how leadership paradigms grounded in proactive engagement and institutional trust-building underpin strategic stability. Through qualitative exploration of policy frameworks, joint-training protocols, and senior-level military diplomacy, the author elucidates three emergent leadership modalities hierarchical command, strategic-diplomatic engagement, and adaptive hybrid models each contributing to the cohesion and resilience of regional security regimes. The findings suggest that military leadership which integrates diplomatic acuity with operational command fosters environments conducive to cooperative security, challenging traditional depictions of military hierarchies as rigidly coercive. Drawing on theoretical insights from regional security studies, the paper contends that defense diplomacy enacted by military leaders can catalyze institutional legitimacy, enhance crisis responsiveness, and strengthen trust across state and alliance networks. Ultimately, the article proposes a reconceptualization of military leadership in international security theory, emphasizing its dual role as a driver of both strategic stability and normative institutionalization. The conclusion underscores the imperative for comprehensive leader development programmes that fuse diplomatic competence with operational expertise, advocating policy frameworks that institutionalize defense diplomacy as a pillar of regional security governance.